Recovery and Then Individual Separation of Platinum, Palladium, and Rhodium from Spent Car Catalytic Converters Using Hydrometallurgical Technique followed by Successive Precipitation Methods. (25th September 2019) - Yousif, Ahmed M.
Abstract : Recovery of PGMs (especially rhodium, platinum, and palladium) from different spent manufactured products (like catalytic converters) is considered as an important task as they are rarely found in nature, and they possess high economic value. In this work, the honeycomb of a car catalytic converter was primarily processed by crushing, grinding, and then treating in a hydrogen atmosphere. In order to establish an economic and ecofriendly method for the recovery of studied PGMs, different experimental conditions of changing HCl/H2 O2 (as a leaching solution) ratio, temperature, and contact time were studied through batch experiments to obtain the optimum leaching conditions. The use of 0.8 vol% H2 O2 and 9.0 M HCl mixture at 60°C for a contact time of 2.5 hours during the leaching process may be considered as the best conditions to be followed to save chemicals, energy, and time (about 86%, 96%, and 98% of Rh, Pt, and Pd were recovered, respectively). Individual separation of PGM ions from each other using precipitation technique from their leaching liquor was performed where % purity values of 99.5, 99.3, and 95.5 were obtained for Pt, Pd, and Rh, respectively.